Growth, productivity and economics of fenugreek (Trigonella foenum-graecum)- pearl millet (Pennisetum glaucum) cropping system as influenced by phosphorus, zinc and zinc solublizer - KUMAWAT, S; SAMMAURIA, R (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted in split plot design with three replications during winter and rainy seasons of 2015–17 at Rajasthan Agriculture Research Institute (RARI), Durgapura-Jaipur to study the growth, productivity and economics of fenugreek (Trigonella foenum-graecum)-pearl millet (Pennisetum glaucum) cropping system by using four levels of phosphorus (0, 20, 40 and 60 kg P2O5/ha) and six treatments of zinc and zinc solubilizer (0, 2.5 and 5.0 kg Zn/ha, zinc solubilizer (Bacillus endophyticus), 2.5 kg Zn/ha + zinc solubilizer and 5 kg Zn/ha + zinc solubilizer) applied to fenugreek. Results revealed that application of 40 kg P2O5/ha and 5 kg Zn/ha + zinc solubilizer resulted in significant increase in all growth and yield attributes while application of 60 kg P2O5/ha and 5 kg Zn/ha + zinc solubilizer increased 37% and 26%, respectively, higher seed yield of fenugreek, when compared to control (1367 and 1340 kg/ha). Residual effects of 60 kg P2O5/ha and 5 kg Zn/ha + zinc solubilizer applied to fenugreek increased grain yield of pearl millet up to 2400 kg/ha and 2375 kg/ha, respectively. Combined application of 60 kg P2O5/ha and 5 kg Zn/ha + zinc solubilizer resulted in the highest yield of fenugreek. The net return and B:C ratio was also the highest in 60 kg P2O5/ha and 5 kg Zn/ha + zinc solubilizer. Thus application of 60 kg P2O5/ha and 5 kg Zn/ha + zinc solubilizer to fenugreek improved the productivity and economics of the fenugreek –pearl millet cropping system.